Analyses and research of needs and possibilities of protection against noise in surrounding of provincial roads in Silesian Voivodship - Tabor, Zbigniew; Bohatkiewicz, Janusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
One of the tasks of provincial road administration authorities is road maintenance ensuring that the noise impacts coming from road traffic are restricted to the limit values. Due to the large volume of traffic, limited availability of space and limited resources, this task is practically impossible to perform. Nowadays, the primary objective of the reconstruction of provincial roads is the road surface improvement. In many places it requires large financial expenses. For several years, some provincial roads authorities have taken first attempts to combine the needs of resurfacing with acoustic protection by using noise reducing road surfaces. Provincial Roads Authority in Katowice took action in this area using existing national and foreign experiences associated with the use of noise reducing surfaces. These activities focused mainly on the selection of types of road surfaces that would be used on the provincial roads of Silesian Voivodship and criteria that indicated the order in which road sections would be rebuild – systematic pavement replacement is needed. Prioritization of the activities and selection of the road sections planned for the reconstruction or renovation were obtained by taking into account several criteria: the results of the noise control plans, condition of the existing pavements, interventions of the inhabitants and investment plans which included the needs of the development of the road network. The article presents the results of the analysis and research on the usage of noise reducing surfaces and the selection of priority sections of provincial roads of Silesian Voivodship planned to be rebuild. The article present a joint result of the cooperation between Provincial Roads Authority in Katowice and the Department of Roads and Bridges (Lublin University of Technology).